Complete Rockall Score in Predicting Outcomes in Acute Upper Gastrointestinal Bleeding - Dewan, Kush Raj; Patowary, Bhanumati Saikia; Bhattarai, Subash; Shrestha, Gaurav (Journal of College of Medical Sciences-Nepal, 2018)
Background: Acute upper GI bleeding is a common medical emergency with a hospital mortality of approximately 10%. Higher mortality rate is associated with rebleeding. Complete Rockall scoring system identifies patients at higher risk of rebleed and mortality. Methods: This is a descriptive hospital based study conducted in Gastroenterology unit of College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal from January 2012 to December 2014. It included 200 patients at random presenting with manifestations of UGI bleed. Complete Rockall score was calculated in each patient and its correlation with mortality and rebleed was determined. Scores of >5 has been considered as one category as it comprises of patients with very high risks and scores of 0-4 as another category of low or lesser risks for the purpose of comparison of different risk factors. Results: Males were predominant (71%). Age ranged from 14 to 90 years, mean being 50.43+17.75 years. At presentation 110 patients (55%) had both hematemesis and malena, 56 patients (28%) had only malena and 34 patients (17%) had only hematemesis. Shock was detected in 21%, severe anemia and high blood urea were found in 31% and 41% respectively. Median hospital stay was 6.5+3.10 days. Comorbidities were present in 83.3%. Complete Rockall score ranged from 0 to 9, mean being 4.30+2.19. One hundred and thirteen (56.5%) had complete Rockall score <4 and 87 (43.5%) >5. Rebleeding was found in 16 (8%) patients. One hundred and eighty eight patients (94%) recovered and discharged from the hospital and 12 patients (6%) expired. The correlations between high Rockall scores (>5) and the occurrence of rebleeding (p=0.001) and mortality (p=0.001) were statistically significant. Conclusion: Acute Upper GI bleeding is a medical emergency. Predictors of mortality in this series were high complete Rockall score >5, esophageal varices with Child Pugh score C, massive initial bleed as well as rebleed and multiple comorbidities. Keywords: acute upper gastrointestinal bleed, complete Rockall score, comorbiditis, rebleed, mortality